Investigación la flexibilidad en la arquitectura (2023)
In this research, through educational equipment for early childhood with flexible spaces, it is possible to break with the socioeconomic gaps imposed by society to train upright citizens, with opportunities and who develop their skills in the best way, innovate in the construction forms and school design respond to the public competition for the architectural draft innovative and sustainable environments for initial education of the district education secretary, creating multipurpose spaces for quality, sustainable education for all.